Sodicity and Salinity Hazards in Water Flow Processes in the Soil - R. P. Dhok; A. S. Patil; V. S. Ghole (E-Journal of Chemistry)
Groundwater is one of the natural resource with the potential for domestic, agricultural and industrial consumption. This paper presents the results of the distribution of salinity characteristics (electrical conductivity and sodium adsorption ratio) of groundwater and based on the results, the evaluation of the sodicity and salinity hazards or in the processes if such groundwater is used for such purposes has been restrictive. This is because of the salinization of aquifers generated by rock salt present below the aquifers. The issue was studied for the groundwater environment in the Karha river basin area, Baramati, Pune, (M.S.) India, for the period of September 2009 to August 2010. The measured data were presented in the form of graphical attachments. The average annual values of the electrical conductivity of groundwater ranged from 490 to 8920 µS/cm in the examined period. Data obtained from analysis signifies the salinity of groundwater in study area is high to very high salinity and can’t be used for crops in a soil with restricted drainage but it can be used under very special circumstances. The sodium adsorption ratio values indicate low, medium to high sodium salinization of the groundwater.